Reflexives : forms and functions - Frajzyngier, Zygmunt; Curl, Traci S. (Typological studies in language ;, 2000)
The importance of reflexive markers in the study of language structure cannot be underestimated: they participate in the coding of the argument structure of a clause; in the coding of semantic relations between arguments and verbs; in the coding of the relationship between arguments; in the coding of aspect; in the coding of point of view; and in the Coding of the information structure of a clause. The present volume offers an approach to reflexive forms and functions from several perspectives: a formal approach where reflexives are discussed within a well-defined model of language representati.